Programming with Examples to Develop Data-Intensive User Interfaces. - Kato, Jun; Igarashi, Takeo; Goto, Masataka (Computer (00189162), 2016)
The programming-with-examples workflow lets developers create interactive applications with the help of example data. It takes a general programming environment and adds dedicated user interfaces for visualizing and managing the data. This lets both programmers and users understand applications and configure them to meet their needs.